STUDI KERUSAKAN HIGH PRESSURE TURBINE VANE PESAWAT ATR72-500 WINGS AIR DI BANDARA SULTAN SYARIF KASIIM II PEKANBARU - Muhammad Desmico Ekta W; Abrar Ridwan (Jurnal Surya Teknika, 2020)
The aircraft can fly as there is a thrust from the engine that causes the aircraft to have speed. The components of the aircraft engines are compressor, combustion chamber, turbine and propeller. High pressure turbine vanes is a component in the Hot section or turbine section that serves to direct the hot gas flow from the combustion chamber to the turbine. The purpose to be achieved in this research is to analyze and find out the cause of high pressure turbine vane damage and know the gas engine efficiency PW127. Cause of damage due to treatment not done according to the schedule until the phenomenon of overtemperature after combustion chamber and the content of impurities in the water laundering results. After the Brayton cycle calculation is obtained the temperature value of the turbine entry 1563oC (1836 K). These results exceed the turbine inlet temperature according to manual maintenance engine. Based on laboratory test, the content of 250 mg/m2 sulfur and 1800 mg/m2 chloride is obtained. This content causes damage by erosion or corrosion of high pressure turbine vane components. The value of gas efficiency is 42% according to the outside Air tempetarure. The thermal efficiency of gases will increase with increasing temperature conditions.